2005
DOI: 10.1080/13811110590512930
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation among Help-Seeking Adolescents: Association with a Negative Self-Image

Abstract: Self-image and factors associated with suicidal ideation were studied among adolescents (N=168, age 17.7+/-2.3 years, 72% girls) seeking psychiatric assessment. The Structured Clinical Interview, Beck Depression Inventory and Offer Self-Image Questionnaire were used. Suicidal ideation (SI) was reported by 64% of subjects, of whom 20% received no psychiatric diagnosis and 58% had depressive disorders. SI in boys associated with being bullied at school and talking about one's problems only with friends, and in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
0
12
1
Order By: Relevance
“…Our results share similarities with a previous Finnish cohort study that reported a significant association between bullying victimization and suicidal behavior only among young females after controlling for conduct and depression symptoms (Klomek et al, 2009). In contrast, male adolescents who were victims of bullying were found to be at greater risk for suicidal ideation (Laukkanen, Honkalampi, Hintikka, Hintikka, & Lehtonen, 2005). A meta-analysis that examined gender childhood victimization and psychiatric outcomes found no definitive answer whether gender moderated the effects of childhood victimization on psychiatric outcomes (Gershon et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Our results share similarities with a previous Finnish cohort study that reported a significant association between bullying victimization and suicidal behavior only among young females after controlling for conduct and depression symptoms (Klomek et al, 2009). In contrast, male adolescents who were victims of bullying were found to be at greater risk for suicidal ideation (Laukkanen, Honkalampi, Hintikka, Hintikka, & Lehtonen, 2005). A meta-analysis that examined gender childhood victimization and psychiatric outcomes found no definitive answer whether gender moderated the effects of childhood victimization on psychiatric outcomes (Gershon et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…3 Findings with respect to gender differences are mixed: some studies suggest greater suicide risk for girls who are victims of bullying 4 and others indicate greater risk for boys who are victims of bullying. 5 No singular type of bullying has emerged as the strongest predictor of suicidal ideation and behaviors; victims, perpetrators, and those who are both victims and perpetrators (ie, bully-victims) have all been implicated as groups likely to consider or attempt suicide. 6–9 …”
mentioning
confidence: 99%
“…In fact, among adults, both depression and alcohol use disorders have been reported to mediate the relation between suicidality and ACEs (Dube et al, 2001(Dube et al, , 2002Felitti et al 1998). Both interpersonal difficulties (Johnson et al, 2002) and family factors influence suicidal behavior in adolescents (Laukkanen, Honkalampi, Hintikka, Hintikka, & Lehtonen, 2005;Randall, Doku, Wilson, & Peltzer, 2014). Interestingly, in a longitudinal study by Johnson et al (2002), interpersonal difficulties mediated the association between maladaptive parenting and offspring's later suicidality.…”
Section: Factors Mediating the Relationship Between Aces And Suicidalitymentioning
confidence: 95%
“…The questionnaire assesses psychological adjustment based on psychodynamic growth and developmental theory. The above-mentioned three dimensions of self-image are known to be risk factors for adolescents' suicidality (Cetin, 2001;Laukkanen et al, 2005). Items are rated on a six-point Likert scale, ranging from "describes me very well" (1) to "does not describe me at all" (6).…”
Section: Methodsmentioning
confidence: 99%